Two new species of the genus Feltria Koenike, 1892, with notes on the water mite fauna of Kyrgyzstan (Acari, Hydrachnidia) - Pešić, Vladimir; Smit, Harry (Zootaxa, 2025)
The knowledge of the water mite fauna of Kyrgyzstan is far from complete. In this study, two species, i.e. Feltria (Feltria) kyrgyzica sp. nov., and F. (Feltria) tienshanensis sp. nov., are described new to science; F. (Feltriella) rubra Piersig, 1898 is reported for the first time for Kyrgyzstan. An updated checklist of the water mite fauna of Kyrgyzstan is given, now including 48 species.